Preliminary use of DNA sequences for Dohrniphora (Diptera: Phoridae) phylogeny and taxonomy JOHN M. HASH, BRIAN V. BROWN & PAUL T. SMITH (USA) - Hash, John M.; Brown, Brian V.; Smith, Paul T. (Zootaxa, 2011)
Phylogenetic analysis of DNA sequence data from the nuclear CAD (rudimentary) and mitochondrial NDI, COI, and 16S gene regions (2817 bp total) recovered exemplars of the genus Dohrniphora as a monophyletic lineage. The data also supported the sister-group relationship of Dohrniphora + Diplonevra and were used to associate a morphologically dissimilar male and female of the species D. ecitophila. Further, we discuss the implications of this designation and provide support for the synonymy of D. ecitophila and D. geminata as proposed by Borgmeier (1968).